The incidence and prevalence of patients with paroxysmal nocturnal haemoglobinuria and aplastic anaemia PNH syndrome: A retrospective analysis of the UK's population‐based haematological malignancy research network 2004‐2018. (9th June 2021) - Richards, Stephen J.; Painter, Daniel; Dickinson, Anita J.; Griffin, Morag; Munir, Talha; Arnold, Louise; Payne, Daniel; Pike, Alexandra; Muus, Petra; Hill, Anita; Newton, Darren J.; McKinley, Claire; et al.
Abstract: Objectives: A retrospective population‐based study to determine the incidence and prevalence of patients with the rare blood disease paroxysmal nocturnal haemoglobinuria (PNH). Methods: All patients were identified by flow cytometric detection of blood cells deficient in glycosylphosphatidylinositol (GPI) linked proteins at a single diagnostic reference laboratory that serves the Yorkshire based, Haematological Malignancy Research Network (HMRN) with a population of 3.8 million. Results: One hundred and ninety‐seven patients with detectable PNH clones at a level of >0.01% in at least two lineages of cells (neutrophils, monocytes and/or red cells) were identified over a 15‐year period (2004‐2018). Of these, 88% had aplastic anaemia (AA), 8% classical PNH and 3% myelodysplastic syndrome. The overall incidence rate was estimated at 0.35 cases per 100 000 people per year. This equates to 220 cases newly diagnosed in the United Kingdom each year. The overall prevalence rate was 3.81 per 100 000, this equates to an estimated 2400 prevalent cases in the UK. The overall and relative 5‐year survival rates were 72% and 82.7%, respectively. Conclusions: This study showed that classical haemolytic PNH is a rare disease and represents only a small proportion overall of patients with detectable PNH cells, the majority of which have aplastic anaemia.